Targeting BRCA and DNA Damage Repair Genes in GI Cancers: Pathophysiology and Clinical Perspectives - Zimmer, Kai; Kocher, Florian; Puccini, Alberto; Seeber, Andreas (Frontiers in Oncology, 2021)
Mutated germline alleles in the DNA damage repair (DDR) genes ‘Breast Cancer Gene 1’ (BRCA1) and BRCA2 have originally been identified as major susceptibility genes in breast and ovarian cancer. With the establishment and approval of more cost-effective gene sequencing methods, germline and somatic BRCA mutations have been detected in several cancers. Since the approval of poly (ADP)-ribose polymerase inhibitors (PARPi) for BRCA-mutated cancers, BRCA mutations gained rising therapeutic implications. The impact and significance of BRCA mutations have been evaluated extensively in the last decades. Moreover, other genes involved in the DDR pathway, such as ATM, ATR or CHK1, have emerged as potential new treatment targets, as inhibitors of these proteins are currently under clinical investigation. This review gives a concise overview on the emerging clinical implications of mutations in the DDR genes in gastrointestinal cancers with a focus on BRCA mutations.